The causal role of gastroesophageal reflux disease in anxiety disorders and depression: A bidirectional Mendelian randomization study - Zeng, Youjie; Cao, Si; Yang, Heng (Frontiers in Psychiatry, 2023)
Background: Observational studies have shown an association between gastroesophageal reflux disease (GERD) and anxiety disorders/depression. However, these evidences may be influenced by confounding factors. Therefore, our study aimed to determine the causal relationship between GERD and anxiety disorders/depression by conducting a bidirectional Mendelian randomization (MR) study. Methods: We performed a bidirectional MR analysis using summary statistics from genome-wide association studies (GWAS) in European individuals. The inverse-variance weighted (IVW) method was used as the primary analytical method to assess causality. In addition, five additional MR methods [maximum likelihood, MR-Egger, weighted median, robust adjusted profile score (MR-RAPS), and mode-based estimate (MR-MBE)] were performed to supplement the IVW results. Furthermore, several sensitivity analyses were performed to assess heterogeneity, horizontal pleiotropy, and stability. Finally, a multivariable MR (MVMR) analysis was performed to determine the causal relationship by adjusting for potential confounders. Results: MR results of the IVW method indicated that GERD significantly increases the risk of anxiety disorders [odds ratio (OR) = 1.35, 95% confidence interval (CI) 1.15-1.59, P = 2.25×10-4] and depression (OR = 1.32, 95% CI 1.15-1.52, P = 1.26×10-4). In addition, the MR results of maximum likelihood, MR-Egger, weighted median, MR-RAPS, and MR-MBE remained parallel to the IVW results. Furthermore, sensitivity analysis suggested that the results were robust, with no pleiotropy or heterogeneity detected. Nevertheless, reverse MR analysis showed that anxiety or depression did not increase GERD risk. Furthermore, MVMR analysis showed that the effect of GERD on increasing the risk of anxiety/depression was independent of confounders. Conclusion: This MR study supports a causal association between GERD and an increased risk of anxiety disorders and depression. Therefore, complementing symptomatic treatment of GERD with psychological assessment and necessary psychological support therapy may help reduce the risk of future anxiety disorders and depression.